Study of Spectroscopy and Thermodynamic Properties for Phoshours dioxide PO2 Molecular and Influence Study of Bond ( P-O ) on Spectroscopy Properties (Baghdad Science Journal, 2012)
In This research a Spectroscopic complement and Thermodynamic properties for molecule PO2 were studied . That included a calculation of potential energy . From the curve of total energy for molecule at equilibrium distance , for bond (P-O), the degenerated of bond energy was (4.332eV) instate of the vibration modes of ( PO2 ) molecule and frequency that was found active in IR spectra because variable inpolarization and dipole moment for molecule. Also we calculate some thermodynamic parameters of ( PO2 ) such as heat of formation , enthalpy , heat Of capacity , entropy and gibb's free energy Were ( -54.16 kcal/mol , 2366.45 kcal/mol , 10.06 kcal /k/mol , 59.52 kcal /k /mol, -15370.51 kcal / mol ) respectively under condition of room temperature and atmosphere pressure ( 298 k , 1 atm.). We calculate there parameters at various temperature from ( 100 – 3000 ) K . It was found that the obtainded results were in a good agreement with previous experimental facts.